Screening of selected parameters of visual system in children at the age of 6 to 10 in Great Poland area - Pieczyrak, Danuta; Miśkowiak, Bogdan (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: The goal of the work was to analyze parameters of visual system in children from Great Poland territory. Research covered: visual acuity and phoria at distance, stereo near vision, colour vision, near point of convergence, plus lens test. Material and methods: 1138 children at the age of 6-10 years were examined, including 88 students in their spectacles. During the examination C-Landolt plates, +1.00 lens, Titmus Stereo Fly test, Ishihara plates, fixation ball and Maddox rod were used. Results: At least 70% children passed particular tests, but the whole examination was passed by only 40% children (in glasses 45% and 15%, respectively); among children who failed plus lens test, 36% did not pass stereotest; 12% of children (35% in glasses), failed stereotest and reached different visual acuity in both eyes, which can cause binocular dysfunction. Conclusions: It is necessary to expand the scope of the school vision screening in school children using additional parameters connected with far and near vision and binocular vision.